Mobile Data Administration System and the Creation Accessoriesnya up Report - author author (Jurnal Sistem Informasi, 2003)
Authors limit the problems ranging from Input Data Mobile and Accessoriesnya to Making Report. To get the output or results desired in accordance with the need to get information or input data that supports this desire. Information on how to be made for computerization and information on how to process transactions performed. Adapaun purpose of creating a computerized system of data processing sales on Mobile and Accessoriesnya among others: Make the check items are available, because the records no longer be processed manually with limited manpower tingat thoroughness. Facilitate the recording of transactions creating an effective reporting and efficient.